Маркетингова взаємодія підприємств у площині глобальних інформаційних потоків - Касян, С. Я. (Видавництво Львівської політехніки, 2012)
Досліджено теоретико-методичні положення маркетингової взаємодії підприємств у площині глобальних інформаційних потоків. Визначено підходи науковців до розвитку ринкової взаємодії у контексті формування маркетингової комунікаційної політики підприємств. Оцінено комунікаційну підтримку в сфері он-лайнового просування програмного забезпечення, високотехнологічних продукції та послуг. Запропоновано схему інтернет-маркетингових комунікацій підприємств, побудовану на засадах соціально-ринкової взаємодії. In an article it is researched theoretical and methodical provisions of marketing interaction of the enterprises in the plane of global information flows. Defined approaches of scientists to development of market interaction in a context of formation of marketing communication policy of the enterprises. Communication support in the sphere of on-line promotion of the software, high-tech production and services is estimated. It is offered the scheme of Internet and marketing communications of the enterprises, constructed on the principles of social and market interaction.
Marketing interaction of the enterprises in the plane of global information flows
Keywords: маркетинг; взаємодія; інформаційні потоки; комунікація; схема; Інтернет; ринок; конкуренти; marketing; interaction; information flows; communication; scheme; Internet; market; competitors